2022
DOI: 10.3389/fphys.2022.1054107
|View full text |Cite
|
Sign up to set email alerts
|

Roles of leptin on energy balance and thermoregulation in Eothenomys miletus

Abstract: Leptin is a hormone mainly synthesized and secreted by white adipose tissue (WAT), which regulates various physiological processes. To investigate the role of leptin in energy balance and thermoregulation in Eothenomys miletus, voles were randomly divided into leptin-injected and PBS-injected groups and placed at 25°C ± 1°C with a photoperiod of 12 L:12 D. They were housed under laboratory conditions for 28 days and compared in terms of body mass, food intake, water intake, core body temperature, interscapular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…9 Similarly, exogenous leptin administration promotes energy metabolism and thermoregulation by regulating corticotropin-releasing hormone (CRH) in Eothenomys miletus. 10 hormone (MCH) levels in combination with a decrease in leptin levels in a cross-sectional study of 108 healthy subjects. 11 The above evidence indicates that attenuation of leptin resistance is strongly correlated to reducing appetite and enhancing energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similarly, exogenous leptin administration promotes energy metabolism and thermoregulation by regulating corticotropin-releasing hormone (CRH) in Eothenomys miletus. 10 hormone (MCH) levels in combination with a decrease in leptin levels in a cross-sectional study of 108 healthy subjects. 11 The above evidence indicates that attenuation of leptin resistance is strongly correlated to reducing appetite and enhancing energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chronic hyperleptinemia lifts the coexpression of NPY and cocaine- and amphetamine-regulated transcripts (CARTs) to increase food intake and reduce energy expenditure . Similarly, exogenous leptin administration promotes energy metabolism and thermoregulation by regulating corticotropin-releasing hormone (CRH) in Eothenomys miletus . Furthermore, a clinical report showed that 2 days of fasting significantly increases circulating melanin-concentrating hormone (MCH) levels in combination with a decrease in leptin levels in a cross-sectional study of 108 healthy subjects .…”
Section: Introductionmentioning
confidence: 99%